Assessing the Factors Influencing Flood Preparedness Among Business Owners in Lagos Island, Nigeria - Alabi, Charles Olabode; Iyalabani, Kamaru Alaba; Mawannomi, Folashade Linda; Babalola, Femi Emmanuel (Journal of Sustainability and Environmental Management, 2024)
This study explores the relationship between factors influencing flood preparedness among business owners in Lagos Island, Nigeria, focusing on who prepares and how they mitigate disaster risks. Data was collected from 325 business owners in flood-prone areas, and Chi-Square hypothesis testing was used to analyze the significance of trust in flood alerts on preparedness. Findings reveal a significant relationship between trust in flood alerts and preparedness levels, with key factors such as flooding causes and duration of residence in floodplain areas influencing readiness. The analysis shows that 70% of respondents had limited access to flood alerts, emphasizing the need for non-technical communication approaches, such as translations, to accommodate cultural diversity. With a p-value of 1.3628 (greater than α = 0.05), the study confirms the impact of trust on preparedness but notes limitations in generalizing findings to areas with less cultural diversity. The research offers strategic insights for disaster management agencies, highlighting the importance of trust-building through non-technical communication to enhance flood preparedness among business owners.